1993
DOI: 10.1029/93pa00060
|View full text |Cite
|
Sign up to set email alerts
|

Microfaunal Evidence for Elevated Pliocene Temperatures in the Arctic Ocean

Abstract: The migration of thermophilic marine Ostracoda into the Arctic Ocean during the Pliocene indicates that winter and summer ocean temperatures around Arctic margins were > 0 øC and > 3 øC, respectively, and that ice-free conditions existed for most or all of the Arctic. By at least 3.5-3.0 Ma, probably earlier, the opening of the Bering Strait allowed marine organisms to migrate through the Arctic Ocean, mostly from the Pacific Ocean. Migrant taxa such as Cythere, Hemicythere, and Neomonoceratina are known from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…The second transition in the Arctic cryosphere, from seasonally ice-free conditions during the middle Pliocene epoch (Cronin et al 1993) to true icehouse conditions characterized by the development of perennial Arctic Ocean sea ice and continental ice sheets in North America and Eurasia, occurred approximately 3 Ma. This transition is particularly intriguing because initial CO 2 concentrations, incident solar radiation, and global geological conditions were comparable to those of BOX 1.…”
Section: Arctic and Global Climate Change In The Pastmentioning
confidence: 99%
“…The second transition in the Arctic cryosphere, from seasonally ice-free conditions during the middle Pliocene epoch (Cronin et al 1993) to true icehouse conditions characterized by the development of perennial Arctic Ocean sea ice and continental ice sheets in North America and Eurasia, occurred approximately 3 Ma. This transition is particularly intriguing because initial CO 2 concentrations, incident solar radiation, and global geological conditions were comparable to those of BOX 1.…”
Section: Arctic and Global Climate Change In The Pastmentioning
confidence: 99%
“…However, extreme warmth documented in marine and terrestrial sequences in the Arctic argues for at least seasonally ice-free conditions (Brouwers, 1994;Cronin et al, 1993;Robinson 2009;Matthiessen et al, 2009). In a fashion similar to the method used in the Southern Hemisphere, modern seasonal growth patterns of sea-ice were used to expand and contract the ice margin from its midPliocene maximum extent (=modern summer extent) to a summer ice-free condition.…”
Section: Sea-ice Extentmentioning
confidence: 99%
“…In a preliminary studies , Joy and Clark [1977) found ostracodes were common in the upper 3 em of core tops from the Canada Basin. Cronin et al [1993Cronin et al [ , 1994 also found that ostracodes occur in Eurasian B asin core tops in water depths from the shelf to >4000 m and that distinct shelf, slope, and deep basin assemblages characterize Arctic Ocean water masses. However, prior ostracode studies lacked quality box core data from deepwater environments of the Canada Basin, and very little was known about deepwater assemblages from areas off Spitsbergen and in the Nordic {Gree nland and No rwe gi an) Seas.…”
Section: Introductionmentioning
confidence: 99%